Pengembangan Media Pembelajaran Interaktif Matematika Berbantuan Adobe Flash Profesional untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik SMP di Kabupaten Bandung - Fadilah, Irma Mardiyati; Rahman, Sidiq Aulia; Nazwa, Ainun; Kosasih, Usep; Maulina, Dhita Nur; Makiah, Umi (Universitas Islam Nusantara, 2023)
This research was conducted because of the low interest and results of students' mathematics learning. In addition, there is no learning media that is interesting and produces student learning. The purpose of this research is to describe the characteristics of professional interactive mathematics learning media assisted by Adobe Flash to increase the interest and learning outcomes of junior high school students. The research method uses the Rzz&D method and experiments with the Dick and Carrey research design. The subjects of this study were class VII junior high school students. The instruments used were validation sheets, student response questionnaires to the media, learning interest questionnaires, and student learning achievement tests. The media corresponded to the problem-based learning model and the discovery learning model. good characteristics to increase interest and learning outcomes and have valid, practical, and effective media qualities.